Compendium of summaries of judicial decisions in environmental-related cases (UNEP NairobiKE, 2007)
Provides compilation of compendium of judicial decisions in environment-related cases. Includes index of cases by continent and, alphabetically by country, as well as by subject matter.
Keywords: ENVIRONMENTAL LEGISLATION